PELAKSANAAN PEMBERIAN KREDIT KEPADA ANGGOTA MASYARAKAT PADA LEMBAGA PERKREDITAN DESA DI KOTA DENPASAR - Indra Parisuda, Komang Gede; Dunia, Ngakan Ketut; Rudy, Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
The existence of Village Credit Institution (LPD) as the village economymediumhave given important meaning for the Denpasar city. Local regulation of Bali ProvinceNumber 3 in 2007 specifythe LPD give loans only to member of the village. Although inreality LPD in Denpasar in their policy also gives credit for the outside residents of thecustom village. Also in LPD credit agreements that have been agreed by both parties.Therefore, this article will explain whether the consideration of the policy implementedby the LPD in Denpasar in lending to the people beyond their custom village. Inaddition, this article also explains the steps that can be conducted by the LPD inDenpasar in the event of borrowers who are in default.
Keywords: Credit, Custom Village, Village Credit Institution